2020
DOI: 10.1021/acsomega.0c04941
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Calculations on the Structural and Electronic Properties of AgAu Alloys

Abstract: In our paper, we study the effects of pseudopotential and concentration of Au doping (0, 25, 50, 75, 100%) on the geometric structure and electronic structures of AgAu alloys. For this purpose, we use ab initio quantum calculations in the Material Studios software. The geometric structures of materials are confirmed through the lattice constant, crystal structure, and total energy of the unit cells (E tot). Electronic structures of the materials are confirmed by band gap (Eg), projected density of states (PDOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Berendsen et al [65] have identified the transition temperature (T m ) of NiAu ranges from T m = 1100 K to T m = 1300 K with Au impurity concentration of 58% [66]. Combined with our recent results as Al [67], FeNi [68], AlNi [69], Ni 1−x Fe x [70], Ni 1−x Cu x [71], Ni [72,73], these results show that the transition temperature (T m ) of Ni material; T m is always proportional with atom number (N), N −1/3 [74,75], and the electronic structure of AuCu [76] and AgAu [77]. The phase transition of Ni material can be determined by stress or temperature [78][79][80][81], and the bonding length of Ni-Ni determined by the experimental method is r = 2.43 Å [82], while the simulation method of Dung, N.T is r = 2.45 Å [73], and P.H.…”
Section: Introductionsupporting
confidence: 75%
“…Berendsen et al [65] have identified the transition temperature (T m ) of NiAu ranges from T m = 1100 K to T m = 1300 K with Au impurity concentration of 58% [66]. Combined with our recent results as Al [67], FeNi [68], AlNi [69], Ni 1−x Fe x [70], Ni 1−x Cu x [71], Ni [72,73], these results show that the transition temperature (T m ) of Ni material; T m is always proportional with atom number (N), N −1/3 [74,75], and the electronic structure of AuCu [76] and AgAu [77]. The phase transition of Ni material can be determined by stress or temperature [78][79][80][81], and the bonding length of Ni-Ni determined by the experimental method is r = 2.43 Å [82], while the simulation method of Dung, N.T is r = 2.45 Å [73], and P.H.…”
Section: Introductionsupporting
confidence: 75%
“…The other five-membered ring molecules and ionization energies (IEs) and the heats of formation of thiophene were calculated and reached a high precision level of ab initio predictions [ 46 ]. Recently, the team members also studied the factors affecting the structural, mechanical, and magnetic properties of metal Fe [ 47 , 48 ], Al [ 49–51 ], Ni [ 52–54 ], Ag [ 55 ], alloys AlNi [ 56 ], NiCu [ 57 , 58 ], FeNi [ 59 , 60 ], AgAu [ 61 ], NiAu [ 62 ], and replace the H derivatives of poly C 13 H 8 OS-H with metal atoms Br, Cu, Kr, Ge, As, Fe [ 63 ] showed that the E g band gap decreased, leading to an increase in the conductivity. The obtained results will contribute to research to find materials new for application in the industrial age.…”
Section: Introductionmentioning
confidence: 99%
“…Metals and interstitial alloys [1][2][3][4][5] have been investigated by several research groups in the last decades due to their applications in various fields [6][7][8][9]. Many theoretical and experimental studies about the mechanical and thermodynamic properties of metals and interstitial alloys gained scientific and technological attention and represent an active area of research that requires integrating modern scientific insights [10][11][12][13][14] from multiple disciplines [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%